KAJIAN YURIDIS TENTANG KEWENANGAN MENTERI DALAM NEGERI MENGAWASI DAN MEMBATALKAN QANUN ACEH - SUHARDI, SUHARDI (Petita : Jurnal Kajian Ilmu Hukum dan Syariah, 2016)
This paper aimed to examine the extent to which the central government through the Minister of Home Affairs monitor and cancel the Aceh Qanun (regional bylaws) and how were the monitoring and cancellation mechanisms of the Qanun as the local regulations with its privilege and exclusivity. The results showed that the monitoring and cancellation of the Qanun by the central government was an error of law. This was because the Qanun was the common legal product of the local executive and legislative, and thus, the cancellation should have been done together with the local government and not unilaterally canceled by the central government. The legal instrument used for the cancellation was the Presidential Decree. In terms of the mechanisms, the central government only focused on the general governance of the Qanun while for the specific areas such as Islamic Sharia, the government monitored and canceled the Qanun through a judicial review by the Supreme Court.